Использование критерия PSNR для оценки качества передачи мультимедийной информаци в системе беспроводного доступа WiMAX - Ивженко, А. В.; Цопа, А. И. (ХНУРЭ, 2011)
The given work is about of searching in field of transmission of multimedia data through wireless radio systems, based on OFDM-modulation technique, such like WiMAX. In this work is given a mathematical model of a system and a radio channel; block of estimation of errors. Based on the model`s results, proposed to add and apply PSNR measure in systems of transmission of multimedia data.
Keywords: качество передачи данных; уровень битовой ошибки